Semi-Empirical AM1 and PM3 Calculations for Electronic Structure of Schiff Base‡ - Arora, Kishor; Gupta, Aarti; Agarwal, D.D. (Asian Journal of Chemistry, 2010)
Schiff bases are widely in use for synthetic purposes both by organic and inorganic chemists. These are stable compounds, which are in use for synthesis of many complexes as ligands such as in the synthesis of complexes of transition metals, lanthanides and actinide metal ions. Experimental data for such compounds are reported by various workers, which prompted us to study the electronic structure of some Schiff basdses using semi-empirical AMI and PM3 quantum chemical calculations. The theoretical studies were done on the Schiff bases of 2-amino pyridine and this study reveals that it is the azomethine group of these schiff bases which act as a site for coordination to metal as it is reported by the coordination chemists.